Effect of Walking on Sand with Dietary Intervention in OverweightType 2 DiabetesMellitusPatients: A Randomized Controlled Trial - Seyam, Mohamed (Healthcare (Basel), 2020)
(1) Background: The primary goal of this study was to assess the effect of sand walking on Hemoglobin A1c (HbA1c), Body Mass Index (BMI), waist circumference, and quality of life among individuals with Type-2 Diabetes Mellitus (T2DM). (2) Methods: A randomized-controlled design was conducted on 66 overweight participants suffering from T2DM. Participants were randomly allocated to sand walking (SW) (n = 33) and normal walking (NW) (n = 33) groups. Participants performed moderate-intensity walking for 30 min, 3 times a week for 4 months. Participants walking on sand had statistically significant mean scores for HbA1c, BMI, waist circumference and quality of life((M = 7.32, SD = 0.47),(M = 25.77, SD = 1.366),(M = 92.94, SD = 2.59), (M = 91.48, SD = 34.08)) than those walking on leveled surface ((M = 8.38, SD = 0.77),t(52.8) = −6.73, p = 0.003, (M = 26.80, SD = 1.38), t(64) = −3.05, p = 0.001,(M = 98.12, SD = 2.16.3), t(64) = −3.75, p = 0.001, (M = 112, SD = 33.7), t(64) = −2.45, p = 0.017)respectively. (3) Conclusions: Regular SW with a healthy dietary regime for 4 months led to a statistically significant difference in HbA1c, BMI, waist circumference, and quality of life as compared to NW group.